Upaya Meningkatkan Kemampuan Berbicara Bahasa Inggris dalam Percakapan Sehari-Hari dengan Metode VAK (Visualization, Auditory, Kinestetic) bagi Para Santri Pondok Pesantren Nurul Huda 2 Tanah Merah - Zulaikah Zulaikah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STKIP Nurul Huda, 2019)
One of the main objectives of learning English in the current era of globalization is ability in English conversation. However, English conversation skills are still considered as one of the difficult skills for santri in the Pesatren of Nurul Huda 2 Tanah Merah. Many santri face some difficulties when they want to communicate in English, even though they have learned English for many years. As a solution to motivate students to learn and communicate in English, that is by providing attractive teaching media through effective learning methods. In this service the method used is using VAK (Visualization, Auditory, and Kinestetic) media. One of the results and benefits of this service activity is to provide knowledge about the media and English conversation learning methods to increase students' interest in learning and communicating in English every day.